2005
DOI: 10.2307/25065363
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic significance of the rpoA loss in the chloroplast genome of mosses

Abstract: A recent survey of arthrodontous mosses revealed that their chloroplast genome lacks the gene encoding the alpha subunit of the RNA polymerase (i.e., rpoA), and that at least in Physcomitrella patens the gene has been transferred to the nuclear genome. Subsequently the gene was recorded from the cytoplasmic genome in Takakia and Sphagnum. Here we extend the survey to representatives of all major lineages of mosses to determine when in the evolutionary history of the Bryophyta the loss took place. Amplification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…A subsequent study (Sugita et al 2004) confirmed the absence for four other 'true' mosses (compare Tortula ruralis, Oliver et al 2010), whereas in the basalmost lineages (Sphagnophytina, Takakiophytina) it was present, situated between rps11 and petD in the LSC. Goffinet et al (2005) again expanded the survey of presence/absence of rpoA in mosses, and concluded that the absence of rpoA is characteristic for all peristomate-arthrodontous mosses (Bryopsida), except Buxbaumiidae, as well as the nematodontous Tetraphidopsida.…”
Section: Other Plastid Markersmentioning
confidence: 97%
“…A subsequent study (Sugita et al 2004) confirmed the absence for four other 'true' mosses (compare Tortula ruralis, Oliver et al 2010), whereas in the basalmost lineages (Sphagnophytina, Takakiophytina) it was present, situated between rps11 and petD in the LSC. Goffinet et al (2005) again expanded the survey of presence/absence of rpoA in mosses, and concluded that the absence of rpoA is characteristic for all peristomate-arthrodontous mosses (Bryopsida), except Buxbaumiidae, as well as the nematodontous Tetraphidopsida.…”
Section: Other Plastid Markersmentioning
confidence: 97%
“…Gene loss can be a powerful phylogenetic marker, as has been shown in mosses, where transfer of the rpoA gene to the nuclear genome denotes a clade comprising nearly 90% of moss species (Sugita et al 2004, Goffinet et al 2005). However, a wider taxonomic survey for presence/loss of the cysA and cysT genes shows that these have most likely been lost multiple times in hepatics (Wickett et al, unpubl.…”
Section: Introductionmentioning
confidence: 99%
“…changes in gene order, gene duplication and loss) are thought to be relatively rare. Plastid genome rearrangements have proved informative in many groups including embryophytes (Kelch et al 2004, Mishler & Kelch 2009), vascular plants (Raubeson & Jansen 1992), ferns (Stein et al 1992), Asteraceae (Jansen & Palmer 1987) and recently in mosses (Goffinet et al 2005(Goffinet et al , 2007; rearrangements in mitochondrial gene order have also provided supporting information for liverwort relationships inferred from DNA sequence data (e.g. Wahrmund et al 2008, Knoop 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The rpoA gene seems to have been lost in Polytrichaceae. The absence of this gene had been reported in T. pellucida as well as in all arthrodontous groups [53,54]. Goffinet et al [55] showed that rpoA does not seem to have been lost in Polytrichum pallidisetum Funck.…”
Section: Discussionmentioning
confidence: 91%